2021
DOI: 10.1371/journal.pone.0248963
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cytology and associated factors among tribal women of Karnataka, India

Abstract: Background Reproductive well-being is a crucial element of women’s health. Due to the asymptomatic nature of gynaecological morbidities, women rarely seek medical advice in the initial period leading to delayed diagnosis and poor prognosis of subsequent disease. The present study aimed to explore the cervical cytology and its associated risk factors among women from tribal communities of the southern part of coastal Karnataka, India. Methods Papanicolaou (Pap) smear test was performed among 1140 women from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
5
7
1
Order By: Relevance
“…When asked about sources of information on cervical cancer among those who had knowledge of cervical cancer, out of the 195 respondents, about 45.1% reported television, radio, internet and 45.6% reported health workers. This is different from a study findings from [27] which had 97.1 percent attributing their sources of information about cancer of the cervix to relatives and friends but similar to findings by [28], which found out that majority of the women had their information from the mass media. Another study also done in Ethiopia by [29], also found that most of the women had their information from health workers.…”
Section: Sources Of Knowledge Of Cervical Cancercontrasting
confidence: 99%
See 1 more Smart Citation
“…When asked about sources of information on cervical cancer among those who had knowledge of cervical cancer, out of the 195 respondents, about 45.1% reported television, radio, internet and 45.6% reported health workers. This is different from a study findings from [27] which had 97.1 percent attributing their sources of information about cancer of the cervix to relatives and friends but similar to findings by [28], which found out that majority of the women had their information from the mass media. Another study also done in Ethiopia by [29], also found that most of the women had their information from health workers.…”
Section: Sources Of Knowledge Of Cervical Cancercontrasting
confidence: 99%
“…Discoveries from the analysis proved just 5.4% respondents had taken part in screening for cervical cancer. Though not encouraging, this is by far better than another study conducted and had none of the study participants who had undergone cervix screening for the disease before [27]. Conversely, out from this research agreed with another one conducted in Elmina by [40], to evaluate the knowledge, barriers and practice towards the screening of the ailment.…”
Section: Barriers To Cervical Canacersupporting
confidence: 53%
“…In Nigeria, the prevalence rate of CECA varies from 5%–11.3% in the northern region [ 29 , 30 ], 11.2%–16.5% in the eastern region [ 31 , 32 ] to 13.9%–34.6% in the western region [ 14 , 33 ]. Similar variation was observed in many LMICs with reported rates of 0.2%–12% in India [ 34 , 35 ], 2.5%–5.7% in Saudi Arabia [ 36 ], 3.7% in Ghana [ 37 ], 3.7% in Oman [ 38 ], 3.8% in Jordan [ 39 ], 4.4% in Kuwait [ 40 ], 5.1% in Turkey [ 41 ], 8.7% in Tanzania [ 42 ] and 14.1% in Ethiopia [ 43 ]. Several factors have been shown to account for this variation.…”
Section: Discussionsupporting
confidence: 87%
“…Other reasons could be the high prevalence of reproductive tract infections. The few studies among tribal women on reproductive infection in a southern and northern state of Karnataka and Himachal Pradesh found a prevalence of 12%–14% 29 30…”
Section: Discussionmentioning
confidence: 99%